2022
DOI: 10.1093/rheumatology/keac016
|View full text |Cite
|
Sign up to set email alerts
|

Hyperresponsive cytosolic DNA-sensing pathway in monocytes from primary Sjögren’s syndrome

Abstract: Objectives Cytosolic DNA-sensing pathway stimulation prompts type I IFN (IFN-I) production, but its role in systemic IFN-I pathway activation in primary SS (pSS) is poorly studied. Here, we investigate the responsiveness of pSS monocytes and plasmacytoid dendritic cells (pDCs) to STING activation in relation to systemic IFN-I pathway activation and compare this to SLE. Methods Expression of DNA-sensing receptors cGAS, IFI16, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Diseases such as subtypes of systemic lupus erythematosus (SLE), lupus nephritis (LN), and dermatomyositis, which have been suggested to be triggered by DNA viruses such as EBV, cytosolic dsDNA, or mitochondrial dsDNA, are also expected to be driven (at least in part) by the aberrant activation of cGAS. A prominent role of cGAS in the development of Sjogren’s Syndrome (SS) would not be unexpected since this disease shares many similarities with SLE; this has been confirmed by a recent publication showing hypersensitivity to cGAS/STING activators in SS patients [ 16 ].…”
Section: The Cgas/sting a Nucleic Acid Sensing Pathway Plays A Role I...mentioning
confidence: 99%
“…Diseases such as subtypes of systemic lupus erythematosus (SLE), lupus nephritis (LN), and dermatomyositis, which have been suggested to be triggered by DNA viruses such as EBV, cytosolic dsDNA, or mitochondrial dsDNA, are also expected to be driven (at least in part) by the aberrant activation of cGAS. A prominent role of cGAS in the development of Sjogren’s Syndrome (SS) would not be unexpected since this disease shares many similarities with SLE; this has been confirmed by a recent publication showing hypersensitivity to cGAS/STING activators in SS patients [ 16 ].…”
Section: The Cgas/sting a Nucleic Acid Sensing Pathway Plays A Role I...mentioning
confidence: 99%
“…Pertovaara et al found increased cytokine-induced STAT1 activation in monocytes of SjS patients via flow cytometry (44). Data from another 2 studies also supported the up-regulation of molecules related to the activation of IFN-related signaling in the monocytes of SjS patients (45,46). Therefore, there is good evidence supporting the up-regulation of IFN-related signaling in the monocytes of SjS patients.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have proven the existence of distinct monocyte subsets and they have critical roles in the development of some rheumatic diseases such as SLE and rheumatoid arthritis (RA), and targeting monocytes is a potential treatment for those diseases (17,33). There are also some studies focusing on the roles of monocytes in SjS, and some have shown that aberrant changes in immunophenotypes, intracellular functional pathways and epigenetics exist in SjS patients (20)(21)(22)(23)(24). Those outcomes suggest the key roles of monocytes in the development and progression of SjS, though the underlying mechanisms are largely elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By sensing dsDNA, the cGAS-STING pathway has become a key pathway in autoimmune and inflammatory diseases (Table 1), such as Sjogren's syndrome (52), systemic lupus erythematosus (SLE) (45), and multiple sclerosis (53). As a downstream target of the cGAS-STING pathway, type I interferon serves as a marker and potential therapeutic target of systemic autoimmune diseases (54,55).…”
Section: The Cgas-sting Pathway Is Involved In Autoimmune Diseasementioning
confidence: 99%